Assessment Tools to Measure Students' Learning Outcomes - Arshi Naim (Scholars Digest Publishing, 2022)
In higher educational program it is important to measure Students’ learning outcomes so that University can measure its quality of academic curriculum. To meet this objective it was important to find out the role of assessment techniques on students learning outcomes. For the research purpose, Strategic Management module was selected and two major assessment techniques were implemented, namely Objective Questions and Subjective Questions. Students’ performance for both types of assessment techniques would facilitate in measuring SLOs, therefore variety of objective questions such as multiple choices questions MCQs, match the statements, True or False and Subjective Questions such as knowledge based and cognitive learning based, were assessed and then compared for the sample of 50 final year students. Students were more likely to employ surface learning approaches in the Objective questions, which was assessing knowledge-based (lower levels of) intellectual processing but performed Poor for the same if objective questions were associated with the employment of deep learning strategies. In contrast, students were more likely to employ deep learning approaches when preparing their Subjective Questions which they perceived as assessing higher levels of cognitive processing.